Innate Immunity to Leishmania Infection: Within Phagocytes. (7th July 2014) - Lopes, Marcela Freitas; Costa-da-Silva, Ana Caroline; DosReis, George Alexandre
Abstract : Infection by Leishmania takes place in the context of inflammation and tissue repair. Besides tissue resident macrophages, inflammatory macrophages and neutrophils are recruited to the infection site and serve both as host cells and as effectors against infection. Recent studies suggest additional important roles for monocytes and dendritic cells. This paper addresses recent experimental findings regarding the regulation of Leishmania major infection by these major phagocyte populations. In addition, the role of IL-4 on dendritic cells and monocytes is discussed.